Exploring the origin of the latitudinal diversity gradient： Contrasting the sister fern genera Phegopteris and Pseudophegopteris - SCHNEIDER, Harald; HE, Li-Juan; MARQUARDT, Jeannine; WANG, Li; HEINRICHS, Jochen; HENNEQUIN, Sabine; ZHANG, Xian-Chun (Journal of systematics and evolution : JSE, 2013)
The origin of the latitudinal biodiversity gradient has been studied using various approaches. Here, we employ a comparative phylogenetic approach to infer evidence for the hypothesis that differences in diversification rates are one of the main factors contributing to the assembly of this gradient. We infer the phylogeny of the two sister genera Phegopteris and Pseudophegopteris. The two genera are distinct in their species richness （4 vs. 20 spp.） and their preferences to temperate to subtropical （Phegopteris） or tropical climates （Pseudophegopteris）. Using sequences of three plastid DNA regions, we confirm the monophyly of each genus and infer the inter- and intra-generic phylogenetic differentiation of the sister clades. We recover evidence for distinct net-diversification rate between the two genera, which may be caused either by a higher extinction risk of temperate Phegopteris or a higher speciation rate of tropical Pseudophegopteris. We discuss our results in the context of our current knowledge on the speciation processes of ferns. We conclude on the crucial influence of other factors such as the rise of the Himalaya on the diversification of these ferns.